2022
DOI: 10.2147/jir.s288294
|View full text |Cite
|
Sign up to set email alerts
|

Topical Anti-Inflammatory Agents for Non-Infectious Uveitis: Current Treatment and Perspectives

Abstract: Non-infectious uveitis represents a heterogenous group of immune-mediated ocular diseases, which can be associated with underlying systemic disease. While the initial choice of treatment of non-infectious uveitis depends on a number of factors such as anatomical location and degree of inflammation, topical therapies often remain the initial choice of non-invasive therapy. In this narrative review, we aim to describe the literature on non-infectious uveitis, with specific focus on the current perspective on top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 96 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…Trans-topical delivery involves the instillation of drops or ointments to the ocular surface. Using this route, therapeutics may be delivered to varying depths within the eye ranging from the superficial surface, in the case of keratoconjunctivitis, to the posterior segment in the adjunct treatment of posterior segment uveitis 47 . As the therapeutic target progresses deeper into the eye, it becomes increasingly difficult to identify drugs capable of overcoming the static and dynamic barriers within the eye to reach this target.…”
Section: Resultsmentioning
confidence: 99%
“…Trans-topical delivery involves the instillation of drops or ointments to the ocular surface. Using this route, therapeutics may be delivered to varying depths within the eye ranging from the superficial surface, in the case of keratoconjunctivitis, to the posterior segment in the adjunct treatment of posterior segment uveitis 47 . As the therapeutic target progresses deeper into the eye, it becomes increasingly difficult to identify drugs capable of overcoming the static and dynamic barriers within the eye to reach this target.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, intermediate, posterior and panuveitis require systemic steroid treatment from the beginning due to the low penetrance of topical agents in the posterior eye sector [100]. Intraocular implants with dexamethasone or fluocinolone could be an effective alternative [101,102], minimizing the dose or frequency of administration, but at the same time exacerbating ocular side effects such as cataract formation, ocular hypertension, and glaucoma or chorioretinopathy [103].…”
Section: Treatmentmentioning
confidence: 99%
“…Glucocorticoids are the first-line treatment option for NIU and are mainly used for rapid control of inflammation. Its main mechanism of action is that glucocorticoid molecules bind to soluble receptors in the cytoplasm, and the resulting complex induces or inhibits the transcription of certain mRNAs and down-regulates the expression of pro-inflammatory factors [6] [14], which in turn exerts an anti-inflammatory-action. The main treatment modalities include topical drop therapy, periocular therapy, intravitreal therapy, etc.…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…NIU is more common than infectious uveitis. Studies are showing that it has a prevalence of 41% -55% in China, 35% -43% in Japan, and 25% -45% in India [6]. An epidemiological study found that the prevalence of NIU in Australia was 80% [7].…”
Section: Introductionmentioning
confidence: 99%